Kualitas Pelayanan Pembuatan Kartu Tanda Penduduk Elektronik Di Kelurahan Utan Kayu Selatan - Febriyanti, Dwi; Anggoro, Yanuar Agung (JAMBIS : Jurnal Administrasi Bisnis, 2024)
One public service that is felt directly by the community is electronic identity card (e-KTP). This research aims to determine the quality of service in the manufacture of e-ID card and obstacles faced in the service of making e-KTP in Kelurahan Utan Kayu South, Matraman District of DKI Jakarta province. This research uses qualitative research methods with descriptive approach. The five dimensions of quality services that are Tangible, Reliability, Responsiveness, Assurance and Emphatyused to describe the quality of service making e-ID card in the village Southem Woodlands. Data obtained directly through interviews and observations in Utan Kayu Selatan Village office involving officials and employees of the provider services and communities that receive e-ID card making services. Research results showing the quality of e-KTP service in Utan Kayu Selatan Village has been running well, but has not run optimally. Inhibitors quality of Service is the unavailability of adequate infrastructure to making e-KTP. Repair of problems that hinder service making e-KTP so that services can be maximized.